2020
DOI: 10.3390/molecules25225256
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Optical Detection of Human-Associated Pathogenic Bacteria

Abstract: Bacterial infection is a global burden that results in numerous hospital visits and deaths annually. The rise of multi-drug resistant bacteria has dramatically increased this burden. Therefore, there is a clinical need to detect and identify bacteria rapidly and accurately in their native state or a culture-free environment. Current diagnostic techniques lack speed and effectiveness in detecting bacteria that are culture-negative, as well as options for in vivo detection. The optical detection of bacteria offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 203 publications
0
20
0
Order By: Relevance
“…One alternative method of characterizing bacterial colonies is elastic light-scattering (ELS) technology, which interrogates the whole 3-D volume of a colony using a collimated and coherent light source and projects the interference patterns into 2-D scattering images [ 1 ]. As the unique scatter patterns are generated depending on the colony structure, classification of a bacterial sample has been successfully performed for different genera, species, and some level of strains in different conditions [ 2 ]. For its simple and rapid detection methods, the optical technique has gained interest and attention, which have been expressed in various studies where similar approaches were applied for bacterial colony characterization [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One alternative method of characterizing bacterial colonies is elastic light-scattering (ELS) technology, which interrogates the whole 3-D volume of a colony using a collimated and coherent light source and projects the interference patterns into 2-D scattering images [ 1 ]. As the unique scatter patterns are generated depending on the colony structure, classification of a bacterial sample has been successfully performed for different genera, species, and some level of strains in different conditions [ 2 ]. For its simple and rapid detection methods, the optical technique has gained interest and attention, which have been expressed in various studies where similar approaches were applied for bacterial colony characterization [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…with antibiotic-resistant bacteria) using culture-free methods, directly from patient fluids or even in vivo. 10 SERS also benefits from recent efforts to develop tandem microfluidic devices in order to improve in situ bioanalysis with direct clinical applicability. 7 SERS is regarded as an ultrasensitive technique because it can achieve single-molecule (SM) detection.…”
Section: Introductionmentioning
confidence: 99%
“…The lengthy process of culturing biofilm organisms may be bypassed with optical methods. A review assessed multiple methods of optical identification of bacteria including infrared spectroscopy, Fourier-transformed infrared spectroscopy, ultraviolet resonance, Raman spectroscopy, surface-enhanced Raman spectroscopy, fluorescence spectroscopy, and optical coherence tomography and concluded that Fourier-transformed infrared spectroscopy provides superior use of data particularly linked to large databases of bacterial characteristics [ 53 ].…”
Section: Discussionmentioning
confidence: 99%